Evaluation of Natural Technological Interfaces for Children with Psychomotor Disabilities - Beltramone, D. A.; Tula, S. M.; Rivarola, M. F.; Hidalgo, M. B.; Tancredi, P. D.; Quinteros Quintana, M. L.; Diaz, J. M.; Marcotti, A.; Atea, J. J. (2022)
Fil: Beltramone, D. A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Ingeniería Biomédica; Argentina.